2020
DOI: 10.1039/d0ra00125b
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal adsorption using structurally preorganized adsorbent

Abstract: The adsorbent had two types of functional groups and six binding sites in one coordination unit. The presence of the amide group shows good anti-interference to alkali metals and alkali soil metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…When examining the sensitivity, selectivity, adsorption, and reusability, the use of certain functional organic ligands highlights the metal ions under specific circumstances and reduces the amount of experimental work required. It has been found that several organic materials, nanomaterials, and metalorganic frameworks have good kinetic performances and exhibit high Pb(II) ion adsorption rates [7][8][9][10][11][12][13][14][15][16][17]. However, it has continued to be difficult to regenerate conjugate adsorbent using strong acid, which produces secondary waste.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When examining the sensitivity, selectivity, adsorption, and reusability, the use of certain functional organic ligands highlights the metal ions under specific circumstances and reduces the amount of experimental work required. It has been found that several organic materials, nanomaterials, and metalorganic frameworks have good kinetic performances and exhibit high Pb(II) ion adsorption rates [7][8][9][10][11][12][13][14][15][16][17]. However, it has continued to be difficult to regenerate conjugate adsorbent using strong acid, which produces secondary waste.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The sustainable management of water resources and the constantly deepening water deficit in the world forces the search for new technologies of wastewater treatment and the use of closed water circuits [ 12 , 13 ]. Currently, various methods are used to remove heavy metals from water, such as precipitation [ 14 ], adsorption [ 11 , 15 , 16 , 17 ], ion exchange [ 18 ], reverse osmosis [ 19 ], membrane filtration [ 20 ], electrolysis [ 21 ] and others [ 3 ]. However, many of these methods are associated with recontamination, low efficiency and high costs.…”
Section: Introductionmentioning
confidence: 99%